Significance of HLA in Graves’ disease and Graves’ orbitopathy in Asian and Caucasian populations – a systematic review - Stasiak, Magdalena; Stasiak, Bartłomiej; Zawadzka-Starczewska, Katarzyna; Lewiński, Andrzej (Frontiers in Immunology, 2023)
Graves’ disease (GD) and Graves’ orbitopathy (GO) development were suspected to be HLA-related in both Asian and Caucasian populations. However, most studies were performed with application of serological methods or low resolution genetic typing, which led to inconsistent results even among the same population. The present review is intended to summarize the state-of-art knowledge on the HLA significance in GD and GO in Asians and Caucasians, as well as to find the most significant alleles for each of the populations. PubMed was searched for relevant articles using the following search terms: HLA plus thyroid-associated ophthalmopathy or Graves’ disease or Graves’ orbitopathy or thyroid eye disease or thyroid-associated orbitopathy. In Asian population GD was found to be associated mostly with B*46:01, DPB1*05:01, B*46:01, DRB1*08:02/03, DRB1*16:02, DRB1*14:03, DRB1*04:05, DQB1*05:02 and DQB1*03:03, while DRB1*07:01, DRB1*01:01, DRB1*13:02, DRB1*12:02 are potentially protective. HLA-B*38:02, DRB1*16:02, DQA1*01:02, DQB1*05:02 can be considered associated with increased risk of GO in Asians, while HLA-B*54:01 may play protective role. In Caucasians, C*07:01, DQA1*05:01, DRB1*03, DQB1*02:01, C*07:01 are associated with GD risk while DRB1*07:01, DQA1*02:01 may be protective. Significance of HLA in the course of GD and novel aspects of HLA amino acid variants and potential HLA-based treatment modalities were also discussed.